2022
DOI: 10.1136/annrheumdis-2022-eular.375
|View full text |Cite
|
Sign up to set email alerts
|

Ab0452 age Related Differences in Neuropsychiatric Manifestations Among Systemic Lupus Erythematosus Patients – A Single Rheumatology Centre Experience in Malaysia

Abstract: BackgroundThe prevalence of SLE in Malaysia was reported as 43/100,000 individuals and Chinese (57/100,000) have the highest prevalence followed by Malays (33/100,000) and Indians (14/100,000) [1,2].The American College of Rheumatology established case definitions and categorised neuropsychiatric syndromes into two groups: central and peripheral system involvement. There were studies showed that cognitive impairment is the commonest neuropsychiatric manifestations with a prevalence of 66% [3].ObjectivesTo dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Of the included studies, 11 were prospective cohort or observational studies, [13][14][15][16][17][18][19][20][21][22][23] including 1 post hoc analysis of a prospective observational study. 15 In total, 5 included studies were retrospective observational studies, [24][25][26][27][28] and 9 were cross-sectional studies. [29][30][31][32][33][34][35][36][37] Only 1 study was reported as a qualitative research study 38 and, finally, 1 study was reported as a population-based cohort study.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 11 were prospective cohort or observational studies, [13][14][15][16][17][18][19][20][21][22][23] including 1 post hoc analysis of a prospective observational study. 15 In total, 5 included studies were retrospective observational studies, [24][25][26][27][28] and 9 were cross-sectional studies. [29][30][31][32][33][34][35][36][37] Only 1 study was reported as a qualitative research study 38 and, finally, 1 study was reported as a population-based cohort study.…”
Section: Resultsmentioning
confidence: 99%